2014
DOI: 10.1155/2014/208064
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Use of ProbioticsLactobacillusandBifidobacteriumHas a Prophylactic Effect on the Occurrence and Severity of Pouchitis: A Randomized Prospective Study

Abstract: Aim. The aim of the study was to assess the impact of the long-term use of the composite probiotics in patients after restorative proctocolectomy. Method. Forty-three patients (20 females and 23 males, aged 21 to 68 years) after restorative proctocolectomy were included in the study. After randomization patients were divided into placebo group and treatment group with oral intake of probiotic containing Lactobacillus acidophilus, Lactobacillus delbrueckii subsp. bulgaricus, and Bifidobacterium bifidus. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 22 publications
0
15
0
2
Order By: Relevance
“…33,36,40 Furthermore, numerous clinical studies have reported therapeutic efficacy with the use of D(¡), L(C) and DL-Lactic acid producing bacteria without producing D-Lactic acidosis ( Table 2). [41][42][43][44][45][46][47][48][49][50][51][52][53] The misinterpretation of D-Lactate producing bacteria has created an almost deliberate atmosphere of scientific nonsense regarding D(¡)-Lactate producing probiotics. The net result has some industry suppliers of probiotic formulations hastening to deliver D-Lactate free probiotic formulations together with a misinformed marketing hype that misleads and confuses healthcare practitioners and the public, for nothing more than monetary gain.…”
Section: D(¡)-lactate Producing Bacteriamentioning
confidence: 99%
“…33,36,40 Furthermore, numerous clinical studies have reported therapeutic efficacy with the use of D(¡), L(C) and DL-Lactic acid producing bacteria without producing D-Lactic acidosis ( Table 2). [41][42][43][44][45][46][47][48][49][50][51][52][53] The misinterpretation of D-Lactate producing bacteria has created an almost deliberate atmosphere of scientific nonsense regarding D(¡)-Lactate producing probiotics. The net result has some industry suppliers of probiotic formulations hastening to deliver D-Lactate free probiotic formulations together with a misinformed marketing hype that misleads and confuses healthcare practitioners and the public, for nothing more than monetary gain.…”
Section: D(¡)-lactate Producing Bacteriamentioning
confidence: 99%
“…However, a study of 40 patients randomised to VSL#3 or placebo immediately after IPAA, and followed for 1 year, found that VSL#3 was effective in the primary prevention of pouchitis as only 10% of patients on VSL#3 developed acute pouchitis compared with 40% on placebo 89. Other studies evaluating the efficacy of Lactobacillus , Bifidobacterium and Clostridium butyricum in the primary prevention of acute pouchitis did not show benefit 90 91…”
Section: Probioticsmentioning
confidence: 99%
“…One study did not use an appropriate control group for analysis 14 . Two studies focused on the treatment of postoperative infections with probiotics, as opposed to their use as a preventive treatment 15 , 16 . We could not access the full‐text of another study; we contacted the corresponding author but did not receive a response 17 .…”
Section: Resultsmentioning
confidence: 99%